Plant-Made Bet v 1 for Molecular Diagnosis - Santoni, Mattia; Ciardiello, Maria Antonietta; Zampieri, Roberta; Pezzotti, Mario; Giangrieco, Ivana; Rafaiani, Chiara; Ciancamerla, Michela; Mari, Adriano; Avesani, Linda (Frontiers in Plant Science, 2019)
Allergic disease diagnosis is currently experiencing a breakthrough due to the use of allergenic molecules in serum-based assays rather than allergen extracts in skin tests. The former methodology is considered a very innovative technology compared to the latter, since it is characterized by flexibility and adaptability to the patient’s clinical history and to microtechnology, allowing multiplex analysis. Molecular-based analysis requires pure allergens to detect IgE sensitization and a major goal, in order to maintain the diagnosis cost-effective, is to limit their production costs. In addition, for the production of recombinant eukaryotic proteins similar to natural ones, plant-based protein production is preferred to bacterial-based systems due to its ability to perform most of the post-translational modifications of eukaryotic molecules. In this framework, Plant Molecular Farming (PMF) may be useful, being a production platform able to produce complex recombinant proteins in short time-frames at low cost. As a proof of concept, PMF has been exploited for the production of Bet v 1a, a major allergen associated with birch (Betula verrucosa) pollen allergy. Bet v 1a has been produced using two different transient expression systems in N. benthamiana plants, purified and used in a new generation multiplex allergy diagnosis system, the patient-Friendly Allergen nano-BEad Array (FABER). Plant-made Bet v 1a is immunoreactive, binding IgE and inhibiting IgE-binding to the Escherichia coli expressed allergen currently available in the FABER test, thus suggesting an overall similar though non-overlapping immune activity compared to the E. coli expressed form.